Optimisation of biodegradation conditions for cyanide removal by Serratia marcescens strain AQ07 using one-factor-at-a-time technique and response surface methodology - Karamba K.I.; Ahmad S.A.; Zulkharnain A.; Syed M.A.; Khalil K.A.; Shamaan N.A.; Dahalan F.A.; Shukor M.Y. (Springer-Verlag Italia s.r.l., 2024)
Indexed by WOS/ Scopus